Telmisartan, an Antagonist of Angiotensin II Receptors, Accentuates Voltage-Gated Na+ Currents and Hippocampal Neuronal Excitability - Lai, Ming-Chi; Wu, Sheng-Nan; Huang, Chin-Wei, William (Frontiers in Neuroscience, 2020)
Telmisartan (TEL), a non-peptide blocker of the angiotensin II type-1 receptor, is a widely-used anti-hypertensive agent. Nevertheless, its neuronal ionic effects and how they potentially affect neuronal network excitability remain largely unclear. With the aid of patch-clamp technology, the effects of TEL on membrane ion currents present in hippocampal neurons (mHippoE-14 cells) were investigated. For additional characterization of the effects of TEL on hippocampal neuronal excitability, we undertook in vivo studies on Sprague Dawley (SD) rats using pilocarpine-induced seizure modeling, a hippocampal histopathological analysis, and inhibitory avoidance testing. In these hippocampal neurons, TEL increased the peak amplitude of INa, with a concomitant decline in the current inactivation rate. The TEL concentration dependently enhanced the peak amplitude of depolarization-elicited INa and lessened the inactivation rate of INa. By comparison, TEL was more efficacious in stimulating the peak INa and in prolonging the inactivation time course of this current than tefluthrin or (-)-epicatechin-3-gallate. In the continued presence of pioglitazone, the TEL-perturbed stimulation of INa remained effective. In addition, cell exposure to TEL shifted the steady-state inactivation INa curve to fewer negative potentials with no perturbations of the slope factor. Unlike chlorotoxin, either ranolazine, eugenol, or KMUP-1 reversed TEL-mediated increases in the strength of non-inactivating INa. In the cell-attached voltage-clamp recordings, TEL shortened the latency in the generation of action currents. Meanwhile, TEL increased the peak INa, with a concurrent decrease in current inactivation in HEKT293T cells expressing SCN5A. Furthermore, although TEL did not aggravate pilocarpine-induced chronic seizures and tended to preserve cognitive performance, it significantly accentuated hippocampal mossy fiber sprouting. Collectively, TEL stimulation of peak INa in combination with an apparent retardation in current inactivation could be an important mechanism through which hippocampal neuronal excitability is increased, and hippocampal network excitability is accentuated following status epilepticus, suggesting further attention to this finding.